Epidemiological and characteristic features of childhood fractures - Burak Kaymaz; Nazan Kaymaz (Trends in Pediatrics)
Childhood fractures are becoming an important public health problem around the world due to the increasing incidence. Fractures in children are more than twice as common as in adults. The incidence of pediatric fractures is affected by many factors such as the age and sex of the child and seasonal and sociocultural factors. One of the leading causes of childhood fractures is simple falls and approximately 50% of childhood fractures were reported to occur after a simple fall. On the other hand, childhood fractures are also very common at home or school and after traffic accidents. A child’s bone has a lower density and more porous structure than an adult’s bone. The periosteum of bone in children is thicker and stimulates new bone formation more strongly. As a result, new bone formation is completed in less time. The remodeling potential of a child’s bone is also an advantage that differentiates pediatric treatment from adult treatment. Complications like delayed union, nonunion, re-fracture, myositis ossificans, and joint stiffness are also very rare in children. But physeal damage may cause serious complications like growth arrest or angular deformities. Despite the advancement in technology and increasing options for minimally invasive surgeries, closed reduction and conservative treatment methods are still the mainstay of treatment in children.